A comparative analysis of determinants of West German and Japanese engineering trade patterns - Reinhard Fürstenberg (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
Over the last twenty years there have been numerous studies on the determinants of the international division of labour. Among these only a few have tackled the question of intraindustry international trade, while many studies address themselves to the question whether different endowment with factors of production determines the comparative advantage in international trade. To the extent that a regression analytic approach was chosen, in general, the level of aggregation was comparatively high. The evidence produced there does not contradict the a priori expectations, i.e. the relatively heavy employment of the factor(s) in relatively rich supply leads to a relatively high comparative advantage. Due to the large number of such studies the respective hypotheses have come to be widely regarded as an established theory. Similar studies on a lower level of aggregation may not yield the same results due to complementarities between industries in the same sector of the economy. It may well be that such complementarities are so overwhelmingly important for the choice of location by individual industries that all other economic factors are overruled. Nevertheless it would be very desirable to have such results for at least two reasons first, in order to formulate better suggestions for the conduct of economic policy in particular with respect to the support of structural changes by government action second, in order to make a contribution to the discussion of the relative importance of intra-industry and interindustry international trade since the level of aggregation is used as an important argument here.
Keywords: 330